Efektivitas Group Based Educational Program Terhadap Self Efficacy dan Kepatuhan Pengobatan pada Pasien Diabetes Mellitus: A Systematic Review - Nita Tri Septiana; Tintin Sukartini; Padoli Padoli (FORIKES, 2021)
Background: Group-Based Education Program (GBEP) is an intervention to improve self efficacy and treatment adherence in diabetes mellitus patients. Objective: To explain the effectiveness of group-based education programs on self-efficacy and treatment adherence in patients with diabetes mellitus. Methods: The database used in this studied was Scopus, Springerlink, and PubMed was limited to the last 5 years of publication from 2015 to 2019, full-text article and in English. The keywords used were